Continuous every-single-shot carrier-envelope phase measurement and control at 100 kHz - Hoff, Dominik; Furch, Federico J.; Witting, Tobias; Ruehle, Klaus; Adolph, Daniel; Sayler, A. Max; Vrakking, Marc J. J.; Paulus, Gerhard G.; Schulz, Claus Peter (Optics Letters, 2018)
With the emergence of high-repetition-rate few-cycle laser pulse amplifiers aimed at investigating ultrafast dynamics in atomic, molecular, and solid-state science, the need for ever faster carrier-envelope phase (CEP) detection and control has arisen. Here we demonstrate a high-speed, continuous, every-single-shot measurement and fast feedback scheme based on a stereo above-threshold ionization time-of-flight spectrometer capable of detecting the CEP and pulse duration at a repetition rate of up to 400 kHz. This scheme is applied to a 100 kHz optical parametric chirped pulse amplification few-cycle laser system, demonstrating improved CEP stabilization and allowing for CEP tagging.
CRIS-Team Scopus Importer:2023-04-20